ANALISIS BAURAN PEMASARAN DILIHAT DARI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENYEWA GEDUNG DI PT. BHUMYAMCA SEKAWAN. - Rokhmad Slamet; Gino Saputra (Sekolah Tinggi Manajemen IMMI Jakarta, 2020)
Every company is required to be ready to face increasingly fierce business competition with other companies from around the world to face globalization which is often said to be an era of world without limits. Increasing customer satisfaction for companies in the service sector is very important, because it involves service quality and price which is one step in increasing customer satisfaction. The purpose of this study is how much influence the price of customer satisfaction on tenants at PT. Bhumyamca Sekawan. How big is the influence of service quality on building customer satisfaction at PT. Bhumyamca Sekawan. How big is the influence of price and quality of service together (simultaneous) on customer satisfaction of building tenants at PT. Bhumyamca Sekawan. Evident Judging from the results of the study that the relationship between price and customer satisfaction shows the relationship value 0.654 and the relationship of service quality with customer satisfaction shows the relationship value 0.720 both have a strong relationship between price and customer satisfaction and service quality with customer satisfaction has a strong relationship when viewed from the correlation coefficient. And Based on the results of other studies with R2 value of 0.587, the price and service quality have a large simultaneous effect on customer satisfaction at PT. Bhumyamca Sekawan, which is 58.7%. Judging from the t test the price is concluded to provide a significant positive effect on customer satisfaction because it has a value of t count (3.076) t table (2.002). As well as service quality, it is concluded that it has a significant positive effect on customer satisfaction because it has a value of tcount (4.694) t table (2.002). And Judging from the F test produced a significance value of 0.000 0.05 means that the variables are jointly / simultaneously there is an influence on the dependent variable. While F count is 40,498 3.16 means that the independent variables are simultaneously / simultaneously there is an influence on the dependent variable.